Manure marketing in the savannas of Nigeria: implications for sustainable food security - Olayide, O.; Alene, A.; Ikpi, A.; Nziguheba, Generose (2009)
Achieving sustainable food security in Nigeria is feasible through organic farming. However, unavailability and resource constraints hamper the adoption of agricultural inputs; hence the market offers opportunity for use of purchased organic inputs. In assessing the importance of the market, the study developed and employed a socio-economic-ecological-modeling (SEEM) framework in its analyses. Using data from a sample of 320 farm households and manure agents, the study aimed at bridging the knowledge gap on the importance, nature, structure and performance of manure market in northern Nigeria. Results show that cereal-legume-based cropping systems accounted for major use of total manure applied on the farm; maize-based cropping systems received the highest amount of the total manure applied. There was asymmetric information flow in the manure market. The market concentration ratios show that none of the manure agents was sufficient in exercising monopoly power in the manure market. The Gini coefficients of the Lorenz curve analyses further showed considerable degrees of inequalities in the volume of manure marketed by different agents both across the agro-ecological zones and socio-economic domains. Manure marketing was found to be inefficient. Further, manure marketing in the study area is profitable with huge potentials for market development.